1999
DOI: 10.1007/s000370050024
|View full text |Cite
|
Sign up to set email alerts
|

Lower bounds for the polynomial calculus and the Gröbner basis algorithm

Abstract: Razborov (1996) recently proved that polynomial calculus proofs of the pigeonhole principle P HP m n must have degree at least n/2 + 1 over any field. We present a simplified proof of the same result.Furthermore, we show a matching upper bound on polynomial calculus proofs of the pigeonhole principle for any field of sufficiently large characteristic, and an n/2 +1 lower bound for any subset sum problem over the field of reals.We show that these degree lower bounds also translate into lower bounds on the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 14 publications
4
102
0
Order By: Relevance
“…The paper [IPS97] proves that linear lower bound on the proof degree in Polynomial Calculus implies the exponential lower bound on the proof size in Polynomial Calculus under fields. The paper [BGIP99] presents a linear lower bound on the degree of proofs of Tseitin formulas in Polynomial Calculus under fields and rings.…”
Section: Introductionmentioning
confidence: 89%
“…The paper [IPS97] proves that linear lower bound on the proof degree in Polynomial Calculus implies the exponential lower bound on the proof size in Polynomial Calculus under fields. The paper [BGIP99] presents a linear lower bound on the degree of proofs of Tseitin formulas in Polynomial Calculus under fields and rings.…”
Section: Introductionmentioning
confidence: 89%
“…This is the main hurdle in performing our computations. However, for certain problems, lower bounds on the algorithm can be shown to be polynomial [40]. We hope that the specific nature of our problem may induce a non-prohibitive Gröbner reduction.…”
Section: A3 a Brief Glossarymentioning
confidence: 99%
“…This is a parallel to the size-width relation for resolution in [11] discussed above, and in fact [11] can be seen as a translation of the bound in [26] from PC to resolution. This size-degree relation has been used to prove exponential lower bounds on size in a number of papers, with [2] perhaps providing the most general setting.…”
Section: Polynomial Calculusmentioning
confidence: 63%
“…Impagliazzo et al [26] showed that strong degree lower bounds imply strong size lower bounds. This is a parallel to the size-width relation for resolution in [11] discussed above, and in fact [11] can be seen as a translation of the bound in [26] from PC to resolution.…”
Section: Polynomial Calculusmentioning
confidence: 99%